Kesetaraan Gender Berbasis Kejadian 1:26-27; 2:18 Upaya Rekonstruksi Konseptual Kedudukan Laki-laki dan Perempuan di Tengah-tengah Gereja - Ambarita, Eka Agustina; Tarigan, Iwan Setiawan; Silaban, Berton Bostang H. (Institut Agama Kristen Negeri Tarutung, 2023)
The purpose of this research is to describe gender equality based on Genesis 1:26-27; 2:18 and to reconstruct the conceptual position of men and women in the center of the church. The research method of this paper is a qualitative method with a library research approach. This research is explored using the principles of hermeneutics, exegesis and exposition in describing gender equality based on Genesis 1:26-27; 2:18 and reconstruct the conceptual position of men and women in the center of the church. The research was carried out by observing various literary texts according to the topics discussed in the research, then compiling them in a holistic, comprehensive and coherent manner. From the results of hermeneutic studies, exegesis and exposition of Genesis 1:26-27; 2:18, the paradigm which considers that women are lower than men when examined more deeply, turns out that this assumption is refuted, because the Bible teaches the principle of gender equality. Men and women are equal before God as creator. So that no one is looking for a way to determine the truth on their own. They are different to complement each other in order to realize the perfect humanity as God wills. The inequality of men and women is a view that contradicts the message of equality between men and women in Genesis 1:26-27 and 2:18. Keywords: Equality; Gender; Reconstruction; Conceptual; Position